TOTAL WAR (Annual of the Faculty of Philosophy in Skopje, 2024)
Total war continues to be a topic of debate and research in modern conflicts.Technological inventions and the interconnectedness of the global community amplifythe effect of the consequences of warfare. We reexamine the totality of modern armedconflicts through an analysis of the achievement and level of destruction that pose newethical, legal and political challenges. The author answers the questions about: the deeppsychological and political implications that extend beyond the battlefield that transmitin depth and encompass the entire (global) society. We define total war through thecriteria of: intentional targeting of civilians, civilian resources and infrastructure andthe firm control of the population’s behavior through the installation of fear, hatred andtrauma; through the political attempt through the war to gain and consolidate supportamong the people, entailing debates about civil liberties and erosion of democratic principles;the treatment of prisoners and the mass executions of the adversary as well as ourown insufficiently motivated forces and ideologically unfit population; and a possiblecataclysmic scenario of the use of atomic weapons. The analysis emphasizes the complexroles of traditionally non-combatant categories and new technologies and doctrines andtheir impact on the totality of warfare. The position remains that total war is an idealconcept, but also the unanswered question if there are atypicalities of that concept,which is the deviation from the benchmark for how limited the war and its constituentelements are instead of total. The research concludes that total war changes cultures,geopolitical views and international relations, and that its legacy changes the course ofhistory for generations to come.
Keywords: war total; limited; resources; societies